Quezon City at 75 resurgent & resilient - Caruncho, Eric S.; Dalisay, Jose Y., Jr; Guillermo, Alice G.; Lacaba, Jose F.; Samson, Regina A. (Erehwon Artworld Corporation, 2014)
History and commercial development of Quezon City.